ANALYZING THE EFFECT OF EMPLOYEE DEVELOPMENT AND ETHICAL LEADERSHIP ON EMPLOYEE PERFORMANCE (CASE STUDY OF PT. TIRTA INVESTAMA AIRMADIDI) - Bonde, Mentari Glorya (Sam Ratulangi University, 2015)
ABSTRACT The purpose of this research is to analyze the effect of employee development and ethical leadership on employee performance of PT. Tirta Investama Airmadidi. 50 employees of PT. Tirta Investama Airmadidi had used as respondents. The result shows that the employee development and ethical leadership have a positive and significant effect on employee performance simultaneously. And for the partially effect, ethical leadership does have a partial effect on employee performance, but employee development doesn’t have a partial effect on employee performance. As the recommendation, PT. Tirta Investama Airmadidi should be paying attention on how to give a proper training and place the employees in accordance with their competence. Furthermore, the leaders need to build a good relationship with the employees by understanding the employee’s needs. Thus, the employees have a job according to their expertise, and they can work better with the leaders, as to improve the employee performance. Keywords: employee development, ethical leadership, employee performance